Review of the genus Ceratopriomorphus Pic, 1922 (Coleoptera: Lycidae) - Barancikova, Barbora; Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2010)
The Neotropical genus Ceratopriomorphus Pic, 1922 is reviewed. Three species are currently placed in the genus, one of which, C. bolivianus sp. nov., is described here. All diagnostic characters are illustrated, and a key to known Ceratopriomorphus species is given.